Effect of integrated nutrient sources on fodder yield and quality of sweet sorghum [Sorghum bicolor (L.) moench.] and phillipesara (Phaseolus trilobus) intercropping system - Singh, Shyam; Kewalanand, -; Chandra, Ramesh; Dass, Anchal (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif seasons of 2007 and 2008 to evaluate the effect of ecofriendly source of nutrients on fodder production and quality of sweet sorghum and phillipesara intercropping system. The growth parameters, viz. plant height, dry matter accumulation, quality parameters, viz. crude protein content and yield, digestibility and green- and dry-fodder yield of sweet sorghum increased in both sole and intercropping systems due to application of all integrated sources of nutrients; significantly higher values of these parameters were recorded with application of 50% nitrogen through inorganic source + 50% through vermicompost. However, all growth parameters except plant height, and green- and dry-fodder yield of phillipesara were significantly higher under sole crop compared to its intercropping with sweet sorghum. Irrespective of nitrogen sources, intercropping system recorded LER of about 1.5 which indicates tremendous advantage of intercropping sweet-sorghum with phillipesara.Total productivity of the systems in terms of dry ’pachang’ equivalent yield and gross returns were twice higher and B:C ratio was thrice higher in sole cropping of phillipesara than intercropping with sweet sorghum. Among nitrogen sources,supply of 50% of recommended N through inorganic source + 50% through vermicompost was most productive and remunerative.